Competing risks data in clinical oncology - Kim, Haesook Teresa (Frontiers in Oncology, 2024)
Competing risks data analysis plays a critical role in the evaluation of clinical utility of specific cancer treatments and can inform the development of future treatment approaches. Although competing risks data are ubiquitous in cancer studies, competing risks data is infrequently recognized and competing risks data analysis is not commonly performed. Consequently, efficacy of specific treatments is often incompletely and inaccurately presented and thus study results may be interpreted improperly. In the present article, we aim to enhance awareness of competing risks data, provide a general overview and guidance on competing risks data and its analysis using cancer clinical studies.